A non-invasive miRNA-based approach in early diagnosis and therapeutics of oral cancer. (December 2022) - Dar, Ghulam Mehdi; Agarwal, Shreya; Kumar, Arun; Nimisha,; Apurva,; Sharma, Abhay Kumar; Verma, Renu; Sattar, Real Sumayya Abdul; Ahmad, Ejaj; Ali, Asgar; Mahajan, Bhawna; Saluja, Sundeep Singh; et al.
Abstract: Oral or mouth cancer is the 16th most common form of cancer among the world's topmost malignancies. Healthy lifestyle and control of known risk factors can reduce its incidences further. Patients succumb to oral cancer when diagnosed late and lack timely access to tertiary care. Molecular biomarkers might help in early detection of oral cancer. Recently, researchers have identified numerous microRNAs which play a crucial role in promoting and suppressing oral cancers. miRNAs are short non-coding RNA molecules (18–22 nucleotides) that play a pivotal role in regulating gene expression. Understanding the miRNA interplays in oral cancers could augment the development of potential diagnostic, prognostic, and therapeutic tools. Liquid biopsy- a non-invasive approach that has been used lately, allows the determination of miRNAs in biological fluids that play essential roles in tumor suppression and cancer promotion. Herein, we summarize an update on the role of miRNAs in the diagnosis and treatment of oral cancer. Graphical Abstract: ga1 Highlights: Liquid biopsy for detecting oral cancer could fill the blanks in attaining a potential diagnostic method. miRNAs are explored as a new oral cancer diagnostic approach that overcomes tissue biopsy drawbacks and holds promising therapeutic options. Numerous differentially dysregulated miRNAs in serum/plasma/tissues of the OSCC patients have been reported by authors. Various Oncomirs and Tumor Suppressor miRNA as potential therapeutic targets in Oral Cancer have been presented by authors.